1967
DOI: 10.1037/h0025028
|View full text |Cite
|
Sign up to set email alerts
|

Learning from prose material: Length of passage, knowledge of results, and position of questions.

Abstract: 72 college Ss read a 2000-word biographical prose passage. A 2 X 3X2 factorial analysis assessed the effects of position of factual questions within the text, length of passage, and presence of knowledge of results. Posttest analysis focused upon (a) questions which had occurred during reading (retention questions), and (b) questions related to the section of the prose passage not tested by the retention questions (incidental questions). All 3 factors were significant for retention questions; only the position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
79
3

Year Published

1969
1969
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 5 publications
(9 reference statements)
8
79
3
Order By: Relevance
“…Second, with the exception of Experiment 1, no overall differences in recall or recognition were observed between questions preceding and questions following the reading material. These results are in disagreement with those of previous research that has found that orienting tasks or questions following reading materials resulted in greater levels of reader recall or recognition than questions preceding reading materials (Frase, 1967(Frase, , 1968Glover, Plake, & Zimmer, 1982). The current results may well be due to the very small amount of reading material associated with questions (brief sentences or 50 word paragraphs) and the possibility that readers could easily retain the questions in working memory while dealing with the brief segments of prose.…”
Section: Discussioncontrasting
confidence: 57%
“…Second, with the exception of Experiment 1, no overall differences in recall or recognition were observed between questions preceding and questions following the reading material. These results are in disagreement with those of previous research that has found that orienting tasks or questions following reading materials resulted in greater levels of reader recall or recognition than questions preceding reading materials (Frase, 1967(Frase, , 1968Glover, Plake, & Zimmer, 1982). The current results may well be due to the very small amount of reading material associated with questions (brief sentences or 50 word paragraphs) and the possibility that readers could easily retain the questions in working memory while dealing with the brief segments of prose.…”
Section: Discussioncontrasting
confidence: 57%
“…Furthermore, Ss who received written answers to questions did better than Ss who received no feedback. Frase (1967) has supported and extended the findings of Rothkopf (1967).…”
supporting
confidence: 64%
“…To the extent, for example, that pretesting focuses attention toward the subsequent encoding of the specific pretested information, it might draw attention away from the encoding of other information that does not remind the learner of a pretest question (Frase, 1967;Hamaker, 1986;Reynolds & Anderson, 1982;Reynolds, Standiford, & Anderson, 1979), and we postulate that such might be the case when pretested and non-pretested information is related in a competitive manner and the relationship is not established and/or brought to mind in the pretest question. By contrast, the multiple-choice format, we would argue, can serve to make the relationship between pretested and competitive non-pretested information explicit.…”
mentioning
confidence: 99%